Production of Vermi Compost from Organic Waste: A Review - Shah, Heena (International Journal of Pharmaceutical & Biological Archive, 2017)
Generation of the huge amount of organic waste around the world-wide is a major ecological issue. When theseorganic wastes are recycled as manure for crop production & are subjected to the degradation & assimilativecapacity of soil, pollution of streams & rivers receiving these wastes is reduced to a large extent as compared to thedirect disposal in water bodies. Utilization of these organic wastes for productivity process is important foreconomic & environmental reasons. Vermicomposting may be the viable option to handle solid waste. This reviewprovides a general overview of viability of vermicomposting processes as an ecofriendly approach. The approach isbased on that perception that tomorrow’s ecology is more important than today’s economy. The integrated approachof composting and vermicomposting processes provides better results.